2003
DOI: 10.1021/ic034992w
|View full text |Cite
|
Sign up to set email alerts
|

The First Example of a Seven-Coordinate Vanadium(III) Thiolate Complex Containing the Hydrazine Molecule, an Intermediate of Nitrogen Fixation

Abstract: The first example of a seven-coordinate vanadium(III) thiolate complex, [V(PS3' ')(N(2)H(4))(3)] (1), where PS3' ' = [P(C(6)H(3)-3-Me(3)Si-2-S)(3)](3)(-), has been synthesized and characterized. Compound 1 contains a tetradentate ligand (PS3' ') and three hydrazine molecules, forming a capped octahedral geometry. A five-coordinate vanadium(III) complex, [V(PS3)(1-Me-Im)] (2), where PS3 = [P(C(6)H(4)-2-S)(3)](3)(-) and 1-Me-Im = 1-methyl-imidazole, was also obtained. Compound 2 adopts a trigonal bipyramidal geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Electronic spectra were recorded at the range of 300-1100 nm on Hewlett-Packard 8453 spectrophotometer. 1 H and 31 P-{ 1 H} NMR measurements were performed on a BRUKER AMX-400 at ambient temperature. The resonance positions are reported with positive shifts downfield of SiMe 4 as calculated from the residual solvent peaks ( 1 H) or downfield of external 85% H 3 PO 4 ( 31 P).…”
Section: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic spectra were recorded at the range of 300-1100 nm on Hewlett-Packard 8453 spectrophotometer. 1 H and 31 P-{ 1 H} NMR measurements were performed on a BRUKER AMX-400 at ambient temperature. The resonance positions are reported with positive shifts downfield of SiMe 4 as calculated from the residual solvent peaks ( 1 H) or downfield of external 85% H 3 PO 4 ( 31 P).…”
Section: General Considerationsmentioning
confidence: 99%
“…To continue our efforts on studying the chemistry of thiofunctional metal complexes relevant to biological processes, we have extended our interest to molybdenum chemistry [1]. The chemistry of molybdenum-sulfur complexes has drawn much attention due to its biological significance [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Examples of secondary sphere interactions in M–N x H y species are known for other transition metals as well. 17 …”
Section: Introductionmentioning
confidence: 99%
“…This was explained further by Meier et al in terms of the geometric requirements of seven-vs. six-coordination with the former requiring a bite angle that would severely strain a six-membered chelate ring [24]. However, in previous studies of V(III) complexes with a tripodal PS3 ligand and its derivatives (PS3 = trisbenzenethiolatophosphine) by some of us, it was found that the geometries of V(III) complexes are very flexible with little relevance of the size of the chelate ring [43]. Furthermore, the crystal structure of a seven-coordinate complex of sexidentate trdta with Mn(II), [Mn(trdta)(H 2 O)] 2À , has been recently reported [44].…”
Section: X-ray Crystallographymentioning
confidence: 99%